Still searching for (education for) sustainable development – reflections on the need, challenges, and chances of transforming education in the 21st century - Lars Keller (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2020)
Scientific evidence has been put forward over and over again in the past decades that, during the Anthropocene, human impact on the various spheres of the Earth has grown to an extent that actually threatens the overall resilience of the Earth system and thus the basis for the existence of future societies. New concepts to tackle the problems ahead and to regain control about positive future development are urgently needed. Education – or rather the transformation of education – and the possible role of education as a key instrument to reach the Sustainable Development Goals could play a prominent role here. However, as both sustainable development and education for sustainable development are still in their infancy, radical changes of the actual concepts of education (for sustainable development) and a new focus on (constructivist) learning have to be discussed. In this paper, the needs, challenges, and chances of transforming education in and for the 21st century are reflected upon .